Vulnerable adults and the law - Herring, Jonathan (Oxford : Oxford University Press, 2016)
Through an examination of current case law, this book provides the first sustained treatment of vulnerable adults, discussing the legal position of those whose ability to make decisions for themselves is impaired.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 10, 2016).
Keywords: Mental health laws -- Great Britain; Law; Laws of specific jurisdictions & specific areas of law